Non-dispensed prescriptions - A nationwide descriptive study - Heini Kari; Fredriikka Nurminen; Hanna Rättö; Hanna Koskinen (Elsevier, 2024)
Background: Medication non-adherence is associated with suboptimal health outcomes, higher mortality, and increased healthcare costs. Objective: The aim of this study was to estimate the number and share of non-dispensed prescriptions at a national level and in specific patient and medicine subgroups. Methods: The study was a nationwide retrospective register-based study. The data consisted of prescriptions prescribed in Finland in 2020 and dispensed between 2020 and 2022. A prescription was considered non-dispensed if it had not been dispensed within the two-year validity period. For each prescription, information on the patient's birth date, sex, and income as well as details of the prescribed medicine and physician's employment sector (public/private) were collected. Distributions and odds ratios (ORs) with corresponding 95 % confidence intervals (CI) were used in the analyses. Results: Of the 26 million prescriptions, 13.3 % were never filled. Over 1.7 million people (43.3 % of all people with prescriptions issued in 2020) had at least one non-dispensed prescription. The share of non-dispensed prescriptions was lower in men than women (12.9 % vs. 13.5 %; OR:0.95; CI:0.95-0.95). Compared to the youngest age group, the share of non-dispensed prescriptions was lower in the older age groups. The lowest share of non-dispensed medicines was in antineoplastic and immunomodulating agents (7.8 %) and in cardiovascular system medicines (8.1 %), whereas the highest was in dermatologicals (20.2 %). The proportion of non-dispensed prescriptions varied between medicine groups, from 5 % for thyroid therapy to 38 % for other nervous system drugs. The most frequently non-dispensed medications were paracetamol, ibuprofen, and salbutamol. Conclusion: The share and number of non-dispensed prescriptions varied across therapeutic areas, medicine groups, active pharmaceutical ingredients, and patient groups. Healthcare professionals should avoid unnecessary prescribing and improve medication adherence to ensure safer and more effective care.